Transplant Tolerance Induction: Insights From the Liver - Dai, Helong; Zheng, Yawen; Thomson, Angus W.; Rogers, Natasha M. (Frontiers in Immunology, 2020)
A comparison of pre-clinical transplant models and of solid organs transplanted in routine clinical practice demonstrates that the liver is most amenable to the development of tolerance. This phenomenon arises in the absence of stringent conditioning regimens that accompany published tolerizing protocols for other organs, particularly the kidney. The unique immunologic facet of the liver has assisted our understanding of the alloimmune response and how it can be manipulated to improve graft function and survival. This review will briefly address important experimental findings following liver transplantation in both animals and humans, and how these have driven the understanding and development of therapeutic immunosuppressive options. We will discuss the liver’s unique system of immune and non-immune cells that regulate immunity, yet maintain effective responses to pathogens, as well as mechanisms of liver transplant tolerance in pre-clinical models and humans, including current immunosuppressive drug withdrawal trials and biomarkers of tolerance. In addition, we will address innovative therapeutic strategies, including mesenchymal stem cell, regulatory T cells and dendritic cell therapy to promote liver allograft tolerance or minimization and withdrawal of immunosuppression in the clinic.